Pharmacy Workforce Support Personnel - Desselle, Shane P.; Hohmeier, Kenneth C. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book provides research and commentary on pharmacy technicians. It demonstrates how the re-design of pharmacy workflow to incorporate more responsibilities for technicians will free up pharmacist time to provide direct patient care. It also highlights that doing so can be accomplished without compromising-and often even improving upon-patient safety. The book also sheds light on employer needs and on new paradigms in pharmacy technician certification, education, and training. However, it also demonstrates the need for improvements in this area, as well as improvements in pharmacy technician quality of work life, advancement opportunities, and wages. Taken together, the papers in this book demonstrate how the results of recent studies help pave the road for the continued evolution of pharmacy care and the optimal deployment of pharmacy workforce personnel.